PENINGKATAN KEMAMPUAN GURU DALAM PENGELOLAAN PBM MELALUI KEGIATAN SUPERVISI AKADEMIK DENGAN PENDEKATAN KOLABORATIF DI SMAN 1 KERUMUTAN KABUPATEN PELALAWAN PROVINSI RIAU TAHUN PELAJARAN 2021/2022 - MISNARTI MISNARTI (LP2MTBM MAKARIOZ, 2022)
The background of this problem is that the teaching and learning process carried out by teachers is still conventional, namely monotonous learning methods taught by teachers and limited school facilities and infrastructure. The purpose of this study was to describe the improvement of teachers' abilities in managing PBM, through academic supervision activities with a collaborative approach by the school principal. The type of research used in this research is the school action research method (PTS). Location The research was carried out at SMAN 1 Kerumutan, Pelalawan Regency. Time The research was carried out in the second semester of January-June of the 2022 school year. The subjects of the principal's action research were 30 teachers at SMAN 1 Kerumutan, Pelalawan Regency, Riau Province. The technique of collecting data from this school action research is through quantitative data obtained from observation and interviews. The data analysis technique used in this study is quantitative data analysis originating from the acquisition of the instrument. The results showed that after being treated through academic supervision using a collaborative approach by the principal, the teacher's ability to manage PBM had increased. every cycle. The ability to manage PBM teachers at SMAN 1 Kerumutan, Pelalawan Regency, was proven to have increased based on the assessment of the teacher, with a score of 65% in the first cycle and 91% in the second cycle.